A concrete corrosion-resistant coating and a preparation method and application thereof

CN122917630APending Publication Date: 2026-10-16SHANDONG EXPRESSWAY TRANSPORTATION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611045925.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]为了解决上述问题,提供了一种混凝土耐腐蚀涂层及其制备方法与应用,通过采用环氧硅烷与氨基硅烷复配的复合硅烷偶联剂,分步改性纳米二氧化硅,有效抑制纳米填料团聚,强化填料与树脂基体的界面结合力;搭配超支化环氧树脂与聚氨酯丙烯酸酯复配改性基体树脂,辅以有机硅预聚体改性,平衡硬度与柔韧性,解决涂层耐磨与抗开裂无法兼顾的问题;该涂层附着力优异,可有效阻隔氯离子与二氧化碳渗透,满足混凝土结构长效防腐需求

Benefits of technology

1.根据本申请的混凝土耐腐蚀涂层,通过采用环氧硅烷偶联剂与氨基硅烷偶联剂复配的复合硅烷体系,且制备时分步添加两种硅烷,规避硅烷提前自聚失效问题;两种硅烷偶联剂共同作用,有效消除填料与树脂之间的界面缝隙,提升涂层整体附着力,从根源阻断腐蚀介质渗透通道,强化涂层屏蔽防护性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a kind of concrete corrosion-resistant coating and its preparation method and application, belong to corrosion-resistant coating technical field.The concrete corrosion-resistant coating, characterized in that, including A component and B component, the A component, by mass fraction, including water-based epoxy curing agent, composite silane coupling agent, film forming aid, wetting agent, dispersing agent, defoaming agent, thickening agent, composite powder, self-cleaning agent and water-based black paste, the balance is water;The B component is matrix resin.By using composite silane coupling agent, step modification nanometer silicon dioxide, effectively inhibit nanometer filler agglomeration, strengthen the interface bonding force of filler and resin matrix;With hyperbranched epoxy resin and polyurethane acrylate compound modified matrix resin, supplemented with silicone prepolymer modification, balance hardness and flexibility, solve the problem that coating wear resistance and anti-cracking cannot be considered simultaneously;The coating adhesion is excellent, effectively blocks chloride ion and carbon dioxide penetration, meets the long-term anticorrosion demand of concrete structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to a concrete corrosion-resistant coating, its preparation method and application, and belongs to the field of corrosion-resistant coating technology. Background Technology

[0002] Cement-based concrete structures such as highway bridges, elevated guardrails, port terminals, sewage tanks, and underground pipe corridors are exposed to the natural environment for a long time. Chloride ions and carbon dioxide can easily penetrate into the concrete, causing steel corrosion, concrete cracking and spalling, and significantly shortening the service life of the structures.

[0003] Applying corrosion-resistant coatings is currently the most economical and convenient means of preventive protection for concrete. In existing technologies, ordinary epoxy coatings have low crosslinking density and limited resistance to ion penetration, pure organosilicon coatings have poor film continuity, and corrosion-resistant coatings are loose with low wear resistance and mechanical strength. Neither of these can meet the requirements for long-term protection. To improve the corrosion resistance and wear resistance of corrosion-resistant coatings, the industry's conventional improvement method is to introduce nano-fillers such as nano-silica into the coatings. However, existing concrete corrosion-resistant coatings have defects such as easy agglomeration of nano-fillers, weak bonding between fillers and resin interfaces, and inability to achieve a balance between high wear resistance and crack resistance.

[0004] Therefore, there is a need to provide a concrete corrosion-resistant coating that can balance high adhesion, high wear resistance, and crack resistance, and achieve long-term resistance to salt and chloride ion erosion. Summary of the Invention

[0005] To address the aforementioned issues, a concrete corrosion-resistant coating, its preparation method, and its application are provided. This method utilizes a composite silane coupling agent, a mixture of epoxy silane and amino silane, to modify nano-silica in stages, effectively inhibiting the agglomeration of nanofillers and strengthening the interfacial bonding between the filler and the resin matrix. Furthermore, it combines hyperbranched epoxy resin with polyurethane acrylate to modify the matrix resin, supplemented by organosilicon prepolymer modification, balancing hardness and flexibility to solve the problem of simultaneously achieving both wear resistance and crack resistance in the coating. This coating exhibits excellent adhesion and effectively blocks chloride ions and carbon dioxide penetration, meeting the long-term corrosion protection requirements of concrete structures.

[0006] According to one aspect of this application, a concrete corrosion-resistant coating comprises component A and component B, wherein component A, by mass fraction, comprises 22.5-23.5% waterborne epoxy curing agent, 0.8-1.2% composite silane coupling agent, 1.8-2.2% film-forming aid, 0.2-0.3% wetting agent, 0.4-0.6% dispersant, 0.2-0.3% defoamer, 0.4-0.6% thickener, 50-56% composite powder, 1.8-2.2% self-cleaning agent, and 0.4-0.6% waterborne black pigment, with the balance being water; component B is a matrix resin; the mass ratio of component A to component B is 1:(0.9-1.1).

[0007] Specifically, the water-based epoxy curing agent is Zhanxin 613, the film-forming aid is alcohol ester twelve, the wetting agent is BD109, the dispersant is 901, the defoamer is Tego810, the self-cleaning agent is Tego5000N, the water-based black pigment is 9007SD, and the thickener is 50%0620.

[0008] Specifically, the application specifies the composition and ratio of components A and B. Component A uses a water-based epoxy curing agent as the crosslinking core, combined with a composite silane coupling agent to bridge the powder and the organic system. The composite powder provides a rigid barrier structure for the corrosion-resistant coating. Component B serves as the main film-forming component, providing a continuous skeleton. The precise ratio of components A and B ensures that the curing and crosslinking reaction proceeds fully, avoiding imbalances that could lead to insufficient crosslinking and stickiness or excessive crosslinking and cracking of the corrosion-resistant coating. The various additives work synergistically to improve the overall basic anti-corrosion performance of the coating.

[0009] Optionally, the composite powder includes barium sulfate, nano-silica, and titanium dioxide, wherein the mass ratio of barium sulfate, nano-silica, and titanium dioxide is (1~1.1):(0.5~0.7):(1~1.1).

[0010] Specifically, the three powders are compounded to form a graded and dense filled structure. The precise ratio achieves the complementarity of coarse and fine powders, eliminates the filling defects of single powders, and, together with the subsequent silane modification system, allows the inorganic powders to participate in the cross-linking reaction of organic resins, reduces the internal defect channels of the corrosion-resistant coating, effectively blocks the penetration of corrosive media, and synergistically improves the density and physical protection of the coating.

[0011] Specifically, the barium sulfate is 1250 mesh barium sulfate, and the nano-silica is precipitated nano-silica.

[0012] Optionally, the composite silane coupling agent includes an epoxy silane coupling agent and an amino silane coupling agent, wherein the mass ratio of the epoxy silane coupling agent to the amino silane coupling agent is (6~7):(3~4).

[0013] Specifically, the epoxy silane coupling agent preferentially binds to the hydroxyl groups on the surface of nano-silica, sealing the hydrophilic groups of the powder and solving the problem of nanofiller agglomeration, while simultaneously docking with the epoxy groups of component B resin; the amino silane coupling agent can dock with the epoxy curing agent and the resin carboxyl groups to construct multiple covalent cross-linking bonds; the precise ratio of the two achieves effective connection of the three phases of inorganic powder, component A curing agent, and component B matrix resin, greatly enhancing the inorganic-organic interface bonding force and improving the coating adhesion and anti-corrosion durability.

[0014] Optionally, the matrix resin includes hyperbranched epoxy resin emulsion and polyurethane acrylate emulsion.

[0015] Specifically, this application specifies a dual-resin compound. The hyperbranched epoxy resin contains a large number of active epoxy sites and has a high crosslinking density, which can fully react with the aminosilane coupling agent to impart high hardness, high adhesion, and excellent resistance to media corrosion. The polyurethane acrylate has abundant flexible segments, which can alleviate the internal stress of the corrosion-resistant coating caused by epoxy crosslinking and improve the crack resistance and bending resistance of the corrosion-resistant coating. The two resins interpenetrate to form an interpenetrating network structure, which takes into account both the rigid protection and flexible crack resistance of the corrosion-resistant coating, solves the industry pain point that traditional coatings cannot balance hardness and flexibility, and is suitable for concrete substrates to deform without cracking.

[0016] Optionally, the matrix resin is prepared by the following method: S1. Add the hyperbranched epoxy resin emulsion into the reactor and stir and heat it. S2. Add the polyurethane acrylate emulsion and stir at a constant temperature until no layering occurs; S3 is added dropwise to methylphenyl silicone prepolymer, and the mixture is kept warm. S4 is cooled, AMP-95 and polyether leveling agent are added, and the pH is adjusted to 7.5~8.0 and the viscosity to 90~110KU. After cooling to room temperature and filtering, the matrix resin is obtained.

[0017] Specifically, this application first mixes two base resins, then introduces organosilicon prepolymer for graft modification to supplement the resin with silanol active sites, and matches the silanized filler of component A to achieve siloxane crosslinking; in the later stage, the pH and viscosity of the system are precisely controlled to adapt to the acid-base compatibility requirements of the waterborne epoxy system and avoid resin demulsification and instability; this process allows organosilicon segments to be stably grafted onto the resin molecular chain, simultaneously improving the hydrophobicity, impermeability and weather resistance of the corrosion-resistant coating, ensuring that component B can achieve a stable chemical reaction with component A, and improving the overall crosslinking integrity of the coating.

[0018] Optionally, the mass ratio of the hyperbranched epoxy resin emulsion to the polyurethane acrylate emulsion is (4~5):1; the mass of the methylphenyl silicone prepolymer is 6~8% of the sum of the masses of the hyperbranched epoxy resin emulsion and the polyurethane acrylate emulsion; the mass of AMP-95 is 1~1.5% of the sum of the masses of the hyperbranched epoxy resin emulsion and the polyurethane acrylate emulsion; and the mass of the polyether leveling agent is 0.5~1% of the sum of the masses of the hyperbranched epoxy resin emulsion and the polyurethane acrylate emulsion.

[0019] Specifically, this application precisely limits the proportions of each component. A high proportion of hyperbranched epoxy ensures basic corrosion resistance and hardness, while a small amount of polyurethane acrylate precisely controls toughness, avoiding excessive flexible resin that could reduce corrosion resistance. The amount of silicone prepolymer added is limited to ensure sufficient silicone crosslinking sites while avoiding excessive silicone components that could cause the corrosion-resistant coating to soften and reduce mechanical strength. The precise dosage of AMP-95 and polyether leveling agent stabilizes the acid and alkaline environment of the resin system and its application fluidity, preventing the system from thickening and separating during storage.

[0020] Optionally, the temperature of S1, S2, and S3 is 45~55℃; the temperature of S4 is 35~40℃; the stirring speed in S1 is 250~280r / min, and the stirring time is 10~15min; in S3, the heat preservation time is 1~1.5h.

[0021] Specifically, this application specifies the temperature, time, and stirring speed to ensure uniform modification and stable storage of component B, and to ensure stable and controllable crosslinking reaction after subsequent compounding with component A.

[0022] According to another aspect of this application, a method for preparing the above-mentioned concrete corrosion-resistant coating is also provided, comprising the following steps: (1) Put water into the tank, add water-based epoxy curing agent, and stir evenly; (2) Add film-forming aid, wetting agent and dispersant in sequence, stirring for 2-3 minutes after each addition, and stirring for 10-15 minutes after all additions are completed. (3) Add defoamer and stir for 10-15 minutes; (4) Add composite powder and epoxy silane coupling agent, stir and disperse for 15-20 min; then add amino silane coupling agent and continue stirring and dispersing for 10-15 min; (5) Add self-cleaning agent, water-based black pigment, and thickener, stir for 20-25 minutes, and filter to obtain component A; (6) Take component A and component B according to the mass ratio, slowly add component B to component A, stir, and obtain a concrete corrosion-resistant coating.

[0023] Specifically, this application employs a step-by-step feeding and silane step-by-step addition process. First, the additives are pre-dispersed, and then two types of silanes are added sequentially to achieve layered modification of the nanofiller. First, an epoxy silane coupling agent is used to block the hydroxyl groups of the powder, and then an amino silane coupling agent is used to supplement the cross-linking active sites, preventing self-polymerization failure due to premature mixing of the two silanes. Finally, component B is compounded, allowing the modified filler and curing agent in component A to fully contact and react with the resin in component B. This step-by-step preparation avoids mutual interference between materials, improves powder dispersion efficiency, maximizes the modification effect of the composite silane coupling agent, and ensures a more complete and orderly cross-linking reaction among the components within the system.

[0024] Optionally, in step (1), the stirring speed is 250~350 r / min and the stirring time is 10~15 min; in step (2), the stirring speed is 700~800 r / min; in step (3), the stirring speed is 750~850 r / min; in step (4), the stirring speed is 950~1000 r / min; in step (5), the stirring speed is 700~800 r / min; and in step (6), the stirring speed is 400~600 r / min.

[0025] Specifically, the initial low-speed rotation completes the mixing of liquid phase materials to avoid the generation of bubbles; the medium-to-high speed completes the wetting and dispersion of additives to improve the wetting effect of powder; the highest speed is adapted to the dispersion of nano-powder and silane modification, thoroughly breaking down nano-agglomerated particles; the later low-speed mixing of components A and B prevents high-speed shear from destroying the already formed pre-crosslinked structure; the gradient speed matches the interaction requirements of components at each stage, ensuring that the powder is fully dispersed and the silane modification reaction is complete, while avoiding emulsion shear demulsification, thus ensuring the storage stability and film-forming performance of the finished coating.

[0026] According to another aspect of this application, the application of the above-described concrete corrosion-resistant coating or the concrete corrosion-resistant coating prepared by the above-described preparation method in the corrosion protection of cement-based concrete structures is also provided.

[0027] The beneficial effects of this application include, but are not limited to: 1. The concrete corrosion-resistant coating of this application adopts a composite silane system of epoxy silane coupling agent and amino silane coupling agent, and the two silanes are added stepwise during preparation to avoid the problem of premature self-polymerization failure of silanes; the two silane coupling agents work together to effectively eliminate the interface gap between the filler and the resin, improve the overall adhesion of the coating, block the penetration channel of corrosive media from the root, and strengthen the shielding and protective performance of the coating.

[0028] 2. According to the concrete corrosion-resistant coating of this application, component B is a compound of hyperbranched epoxy resin emulsion and polyurethane acrylate emulsion to achieve a balance between the hardness and toughness of the corrosion-resistant coating; the high proportion of hyperbranched epoxy resin has abundant epoxy active groups and high crosslinking density, which can endow the coating with excellent hardness, wear resistance and chemical corrosion resistance; the flexible segments of polyurethane acrylate can release the internal stress generated by epoxy crosslinking, making up for the defects of pure epoxy coatings being brittle and prone to cracking; combined with methylphenyl organosilicon prepolymer modification, the hydrophobicity and impermeability are further improved, solving the industry pain point that traditional corrosion-resistant coatings cannot balance hardness and flexibility, and adapting to the deformation of concrete substrates without cracking.

[0029] 3. According to the concrete corrosion-resistant coating of this application, barium sulfate, nano-silica, and titanium dioxide are compounded to form a multi-graded filling system. The coarse and fine fillers are combined to comprehensively seal the pores of the corrosion-resistant coating. Barium sulfate fills macroscopic pores, enhancing the shielding and barrier capabilities; nano-silica fills microscopic pores, improving wear resistance and density through the nano-effect; titanium dioxide enhances the coating's weather resistance and anti-aging properties. The precise proportioning of the three powders, combined with a multi-linked network, significantly improves the coating's resistance to chloride ions and carbon dioxide penetration, meeting the long-term corrosion protection requirements of concrete structures.

[0030] 4. According to the preparation method of the concrete corrosion-resistant coating of this application, by limiting the process steps and process parameters, the preparation process is simple and controllable, requires no special equipment, is suitable for industrial mass production, and the coating has mild room temperature curing conditions, making on-site construction convenient and applicable to a wider range of scenarios. Detailed Implementation

[0031] The present application is described in detail below with reference to the embodiments, but the present application is not limited to these embodiments.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of skill in the art. The reagents and raw materials used in this invention are readily available through conventional means, and unless otherwise specified, they shall be used in accordance with conventional methods in the art or as per the product instructions. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to the methods of this invention. The preferred embodiments and materials described in this patent are for illustrative purposes only. The waterborne epoxy curing agent used in the following examples and comparative examples is Zhanxin 613, the film-forming aid is alcohol ester dodecyl, the wetting agent is BD109, the dispersant is 901, the defoamer is Tego810, the self-cleaning agent is Tego5000N, the waterborne black pigment is 9007SD, the thickener is 50% 0620, the barium sulfate is 1250 mesh barium sulfate, the nano silica is precipitated nano silica with a particle size of 50nm, the epoxy silane coupling agent is MP200, the amino silane coupling agent is Coatosil 1120, the methyl phenyl organosilicon prepolymer is Shin-Etsu KR-510, and the polyether leveling agent is BYK-333.

[0033] Example 1: Preparation of a Corrosion-Resistant Coating for Concrete Composition A is as follows: 22.5% water-based epoxy curing agent, 0.8% composite silane coupling agent (the mass ratio of epoxy silane coupling agent to amino silane coupling agent is 6:4), 1.8% film-forming aid, 0.2% wetting agent, 0.4% dispersant, 0.2% defoamer, 0.4% thickener, 50% composite powder (the mass ratio of barium sulfate, nano silica, and titanium dioxide is 1:0.5:1), 1.8% self-cleaning agent, and 0.4% water-based black pigment, with the balance being water; The preparation process of component B is as follows: S1. Add the hyperbranched epoxy resin emulsion into the reactor, stir and heat to 45°C, stir at 250 r / min, and stir for 10 min. S2. Add polyurethane acrylate emulsion, and the mass ratio of hyperbranched epoxy resin emulsion to polyurethane acrylate emulsion is 4:1. Stir at a constant temperature of 45℃ until no layering occurs. S3 is added dropwise to methylphenyl silicone prepolymer, the mass of which is 6% of the combined mass of hyperbranched epoxy resin emulsion and polyurethane acrylate emulsion, and kept at 45°C for 1 hour. S4 is cooled to 35°C, and AMP-95 and polyether leveling agent are added. The mass of AMP-95 is 1% of the sum of the masses of the hyperbranched epoxy resin emulsion and the polyurethane acrylate emulsion, and the mass of the polyether leveling agent is 0.5% of the sum of the masses of the hyperbranched epoxy resin emulsion and the polyurethane acrylate emulsion. The pH is adjusted to 7.5 and the viscosity to 90 KU. The mixture is then cooled to room temperature and filtered to obtain the matrix resin.

[0034] The mass ratio of component A to component B is 1:0.9.

[0035] Preparation of corrosion-resistant coatings for concrete: (1) Put water into the tank, add water-based epoxy curing agent, stir evenly, stir speed is 250r / min, and stir time is 10min; (2) Add film-forming aid, wetting agent and dispersant in sequence. Stir for 2 minutes after each addition. After all the ingredients are added, stir for 10 minutes. The stirring speed is 700 r / min. (3) Add defoamer and stir at 750 r / min for 10 min; (4) Add composite powder and epoxy silane coupling agent, stir and disperse at 950 r / min for 15 min; then add amino silane coupling agent, continue stirring and dispersing at 950 r / min for 10 min; (5) Add self-cleaning agent, water-based black pigment, and thickener, stir at 700 r / min for 20 min, and filter to obtain component A; (6) Take component A and component B according to the mass ratio, slowly add component B to component A, stir at 400 r / min to obtain a concrete corrosion resistant coating.

[0036] Example 2: Preparation of a Corrosion-Resistant Coating for Concrete Composition A is as follows: 23% water-based epoxy curing agent, 1% composite silane coupling agent (the mass ratio of epoxy silane coupling agent to amino silane coupling agent is 7:4), 2% film-forming aid, 0.25% wetting agent, 0.5% dispersant, 0.25% defoamer, 0.5% thickener, 52% composite powder (the mass ratio of barium sulfate, nano silica, and titanium dioxide is 1:0.6:1.1), 2% self-cleaning agent, and 0.5% water-based black pigment, with the balance being water; The preparation process of component B is as follows: S1. Add the hyperbranched epoxy resin emulsion into the reactor, stir and heat to 50°C, stir at 260 r / min, and stir for 12 min. S2. Add polyurethane acrylate emulsion, and the mass ratio of hyperbranched epoxy resin emulsion to polyurethane acrylate emulsion is 4.5:1. Stir at a constant temperature of 50°C until no stratification occurs. S3 is added dropwise to methylphenyl silicone prepolymer, the mass of which is 7% of the combined mass of hyperbranched epoxy resin emulsion and polyurethane acrylate emulsion, and kept at 50°C for 1.5 hours. S4 is cooled to 35°C, and AMP-95 and polyether leveling agent are added. The mass of AMP-95 is 1.2% of the sum of the masses of the hyperbranched epoxy resin emulsion and the polyurethane acrylate emulsion, and the mass of the polyether leveling agent is 0.8% of the sum of the masses of the hyperbranched epoxy resin emulsion and the polyurethane acrylate emulsion. The pH is adjusted to 8.0 and the viscosity to 100 KU. The mixture is then cooled to room temperature and filtered to obtain the matrix resin.

[0037] The mass ratio of component A to component B is 1:1.

[0038] Preparation of corrosion-resistant coatings for concrete: (1) Put water into the tank, add water-based epoxy curing agent, stir evenly, stir at 300 r / min, and stir for 12 min. (2) Add film-forming aid, wetting agent and dispersant in sequence. Stir for 3 minutes after each addition. After all the ingredients are added, stir for 12 minutes. The stirring speed is 750 r / min. (3) Add defoamer and stir at 800 r / min for 12 min; (4) Add composite powder and epoxy silane coupling agent, stir and disperse at 980 r / min for 17 min; then add amino silane coupling agent, continue stirring and dispersing at 980 r / min for 12 min; (5) Add self-cleaning agent, water-based black pigment, and thickener, stir at 750 r / min for 22 min, and filter to obtain component A; (6) Take component A and component B according to the mass ratio, slowly add component B to component A, stir at 500 r / min to obtain a concrete corrosion resistant coating.

[0039] Example 3: Preparation of a Corrosion-Resistant Coating for Concrete Composition A is as follows: 23.5% water-based epoxy curing agent, 1.2% composite silane coupling agent (the mass ratio of epoxy silane coupling agent to amino silane coupling agent is 6:4), 2.2% film-forming aid, 0.3% wetting agent, 0.6% dispersant, 0.3% defoamer, 0.6% thickener, 56% composite powder (the mass ratio of barium sulfate, nano silica, and titanium dioxide is 1.1:0.7:1.1), 2.2% self-cleaning agent, and 0.6% water-based black pigment, with the balance being water; The preparation process of component B is as follows: S1. Add the hyperbranched epoxy resin emulsion into the reactor, stir and heat to 55°C, stir at 280 r / min, and stir for 15 min. S2. Add polyurethane acrylate emulsion, and the mass ratio of hyperbranched epoxy resin emulsion to polyurethane acrylate emulsion is 5:1. Stir at a constant temperature of 55℃ until no layering occurs. S3 is added dropwise to methylphenyl silicone prepolymer, the mass of which is 8% of the combined mass of hyperbranched epoxy resin emulsion and polyurethane acrylate emulsion, and kept at 55℃ for 1.5h. S4 is cooled to 40℃, and AMP-95 and polyether leveling agent are added. The mass of AMP-95 is 1.5% of the sum of the masses of the hyperbranched epoxy resin emulsion and the polyurethane acrylate emulsion, and the mass of the polyether leveling agent is 1% of the sum of the masses of the hyperbranched epoxy resin emulsion and the polyurethane acrylate emulsion. The pH is adjusted to 8.0 and the viscosity to 110 KU. The mixture is then cooled to room temperature and filtered to obtain the matrix resin.

[0040] The mass ratio of component A to component B is 1:1.1.

[0041] Preparation of corrosion-resistant coatings for concrete: (1) Put water into the tank, add water-based epoxy curing agent, stir evenly, stir at a speed of 350 r / min, and stir for 15 min; (2) Add film-forming aid, wetting agent and dispersant in sequence. Stir for 3 minutes after each addition. After all the ingredients are added, stir for 15 minutes. The stirring speed is 800 r / min. (3) Add defoamer and stir at 850 r / min for 15 min; (4) Add composite powder and epoxy silane coupling agent, stir and disperse at 1000 r / min for 20 min; then add amino silane coupling agent, and continue stirring and dispersing at 1000 r / min for 15 min; (5) Add self-cleaning agent, water-based black pigment, and thickener, stir at 800 r / min for 25 min, and filter to obtain component A; (6) Take component A and component B according to the mass ratio, slowly add component B to component A, stir at 600 r / min to obtain a concrete corrosion resistant coating.

[0042] Example 4 The difference between Example 4 and Example 2 is that the composite powder does not contain barium sulfate, but all other aspects are the same.

[0043] Example 5 The difference between Example 5 and Example 2 is that the composite powder only contains nano-silica, while the rest are the same.

[0044] Example 6 The difference between Example 6 and Example 2 is that the composite silane coupling agent only includes an epoxy silane coupling agent, while the rest are the same.

[0045] Example 7 The difference between Example 7 and Example 2 is that the composite silane coupling agent only includes an aminosilane coupling agent, while the rest are the same.

[0046] Example 8 The difference between Example 8 and Example 2 is that the mass ratio of epoxy silane coupling agent to amino silane coupling agent is 1:1.

[0047] Example 9 The difference between Example 9 and Example 2 is that the latter does not include polyurethane acrylate, but all other aspects are the same.

[0048] Example 10 The difference between Example 10 and Example 2 is that the mass ratio of hyperbranched epoxy resin emulsion to polyurethane acrylate emulsion is 1:1, while all other aspects are the same.

[0049] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that the latter does not include the composite silane coupling agent; otherwise, they are the same.

[0050] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that the latter does not include the composite powder, while all other aspects are the same.

[0051] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that in step (4), the epoxy silane coupling agent and the amino silane coupling agent are added at the same time and stirred and dispersed at 980 r / min for 29 min, while the rest are the same.

[0052] Test case Standardized test conditions: Standard C30 concrete test blocks were selected as the substrate, and the surface was ground, dusted, and degreased before use; Components A and B were mixed and stirred evenly according to the corresponding ratio, and sprayed to control the dry film thickness to be uniformly 100±5μm; The test samples were placed in a standard environment (temperature 23±2℃, relative humidity 50±5%) for 7 days before performance testing was carried out.

[0053] Experimental Example 1 Adhesion Test The adhesion test was conducted using the pull-off method according to GB / T 5210-2006. The maximum tensile strength at which the coating failed was recorded. Each group of samples was tested in parallel three times, and the average value was taken as the final adhesion data. The test results are shown in Table 1.

[0054] Table 1 Adhesion test results

[0055] Table 1 shows that the adhesion of Examples 1-3 by pull-off method is above 3.8 MPa. Example 2 is the best example. Example 9 has no flexible polyurethane acrylate, and the pure epoxy has a higher crosslinking density and stronger rigidity, resulting in a slight increase in adhesion. In Example 10, the proportion of flexible resin is too high, the resin crosslinking density decreases, and the adhesion decreases. The lack of barium sulfate, single nanofiller, and single silane all reduce the interfacial bonding force. Comparative Example 1 has no silane coupling agent, and Comparative Example 3 has two silane coupling agents added at the same time, resulting in a lack of effective bridging effect, a significant increase in defects at the filler-resin interface, and a decrease in adhesion.

[0056] Test Example 2: Elongation at Break Test The elongation at break was tested according to GB / T 1731-2020. The elongation at break was recorded, and five parallel tests were conducted for each group, with the average value taken. The test results are shown in Table 2.

[0057] Table 2 Results of Elongation at Break Test

[0058] Table 2 shows that the elongation at break decreased in Example 8 and Comparative Example 3. The reasons are that the ratio of composite silane coupling agent was unbalanced and the simultaneous addition of two silane coupling agents would destroy the resin cross-linking network and reduce the deformation capacity. In Example 9, the flexible resin was completely removed, and the elongation at break dropped sharply. In Example 10, the proportion of flexible resin was greatly increased, and the toughness was significantly improved.

[0059] Experiment Example 3 Salt Spray Test Referring to GB / T 10125-2021, the coated test block was placed in a salt spray test chamber, a 5% sodium chloride solution was prepared, the chamber temperature was kept constant at 35℃, and the salt spray deposition was 1.0~2.0mL / 80cm. 2 •h; The sample was placed on an inclined plane with pre-existing scratches on the coating. Continuous spraying and observation were conducted to record the longest duration for blistering, peeling, rusting, and scratch erosion to occur on the coating. The test results are shown in Table 3.

[0060] Table 3 Salt spray test results

[0061] Table 3 shows that Example 2 is the best example, with a salt spray resistance time of up to 1500 hours. The salt spray resistance time of Example 4 decreased because the removal of 1250-mesh barium sulfate resulted in the inability to seal the micron-level macroscopic pores, allowing the salt spray medium to penetrate rapidly. The salt spray resistance of Example 5 deteriorated because the pores could not be effectively filled when only nano-silica was used. The salt spray resistance time of Comparative Examples 1, 2, and 3 decreased significantly, with Comparative Example 1 showing the worst effect. The salt spray resistance of Example 10 decreased because the high proportion of flexible resin reduced the overall density, leading to a decline in salt spray resistance.

[0062] Experimental Example 4: Chloride Ion Permeability Test Referring to GB / T 50082-2009, the resistance of the coating to chloride ion penetration was tested using the electric flux method. The test results are shown in Table 4.

[0063] Table 4 Results of Chloride Ion Permeability Coefficient Test

[0064] Table 4 shows that Example 2 exhibits the best resistance to chloride ion penetration. Examples 4 and 5 show a significant increase in chloride ion penetration coefficient. This is attributed to the lack of coarse-grained barium sulfate and the formation of interconnected pores by the single nanofiller, which multiplies the ion penetration rate. Comparative Examples 1 and 2 show a significant increase in chloride ion penetration coefficient. This is attributed to the absence of a composite silane coupling agent and the simultaneous feeding process, which creates numerous interfacial gaps, allowing chloride ions to easily penetrate the coating and erode the internal steel reinforcement of the concrete, thus increasing the chloride ion penetration coefficient.

[0065] The above description is merely an embodiment of this application, and the scope of protection of this application is not limited to these specific embodiments, but is determined by the claims of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the technical concept and principles of this application should be included within the scope of protection of this application.

Claims

1. A concrete corrosion-resistant coating, characterized in that, The product comprises component A and component B. Component A, by mass fraction, comprises 22.5-23.5% waterborne epoxy curing agent, 0.8-1.2% composite silane coupling agent, 1.8-2.2% film-forming aid, 0.2-0.3% wetting agent, 0.4-0.6% dispersant, 0.2-0.3% defoamer, 0.4-0.6% thickener, 50-56% composite powder, 1.8-2.2% self-cleaning agent, and 0.4-0.6% waterborne black pigment, with the balance being water. Component B is a matrix resin. The mass ratio of component A to component B is 1:(0.9-1.1).

2. The concrete corrosion-resistant coating according to claim 1, characterized in that, The composite powder comprises barium sulfate, nano-silica, and titanium dioxide, wherein the mass ratio of barium sulfate, nano-silica, and titanium dioxide is (1~1.1):(0.5~0.7):(1~1.1).

3. The concrete corrosion-resistant coating according to claim 1, characterized in that, The composite silane coupling agent includes an epoxy silane coupling agent and an amino silane coupling agent, wherein the mass ratio of the epoxy silane coupling agent to the amino silane coupling agent is (6~7):(3~4).

4. The concrete corrosion-resistant coating according to claim 1, characterized in that, The matrix resin includes hyperbranched epoxy resin emulsion and polyurethane acrylate emulsion.

5. The concrete corrosion-resistant coating according to claim 4, characterized in that, The matrix resin is prepared by the following method: S1. Add the hyperbranched epoxy resin emulsion into the reactor and stir and heat it. S2. Add the polyurethane acrylate emulsion and stir at a constant temperature until no layering occurs; S3 is added dropwise to methylphenyl silicone prepolymer, and the mixture is kept warm. S4 is cooled, AMP-95 and polyether leveling agent are added, and the pH is adjusted to 7.5~8.0 and the viscosity to 90~110KU. After cooling to room temperature and filtering, the matrix resin is obtained.

6. The concrete corrosion-resistant coating according to claim 5, characterized in that, The mass ratio of hyperbranched epoxy resin emulsion to polyurethane acrylate emulsion is (4~5):1; the mass of the methylphenyl silicone prepolymer is 6~8% of the sum of the masses of the hyperbranched epoxy resin emulsion and the polyurethane acrylate emulsion; the mass of AMP-95 is 1~1.5% of the sum of the masses of the hyperbranched epoxy resin emulsion and the polyurethane acrylate emulsion; and the mass of the polyether leveling agent is 0.5~1% of the sum of the masses of the hyperbranched epoxy resin emulsion and the polyurethane acrylate emulsion.

7. The concrete corrosion-resistant coating according to claim 6, characterized in that, The temperatures of S1, S2, and S3 are 45~55℃; the temperature of S4 is 35~40℃; the stirring speed in S1 is 250~280r / min, and the stirring time is 10~15min; in S3, the heat preservation time is 1~1.5h.

8. The method for preparing the concrete corrosion-resistant coating according to any one of claims 1 to 7, characterized in that, Includes the following steps: (1) Put water into the tank, add water-based epoxy curing agent, and stir evenly; (2) Add film-forming aid, wetting agent and dispersant in sequence, stirring for 2-3 minutes after each addition, and stirring for 10-15 minutes after all additions are completed. (3) Add defoamer and stir for 10-15 minutes; (4) Add composite powder and epoxy silane coupling agent, stir and disperse for 15-20 min; then add amino silane coupling agent and continue stirring and dispersing for 10-15 min; (5) Add self-cleaning agent, water-based black pigment, and thickener, stir for 20-25 minutes, and filter to obtain component A; (6) Take component A and component B according to the mass ratio, slowly add component B to component A, stir, and obtain a concrete corrosion resistant coating.

9. The method for preparing a corrosion-resistant coating for concrete according to claim 8, characterized in that, In step (1), the stirring speed is 250~350 r / min and the stirring time is 10~15 min; in step (2), the stirring speed is 700~800 r / min; in step (3), the stirring speed is 750~850 r / min; in step (4), the stirring speed is 950~1000 r / min; in step (5), the stirring speed is 700~800 r / min; in step (6), the stirring speed is 400~600 r / min.

10. The application of the concrete corrosion-resistant coating according to any one of claims 1 to 7 or the concrete corrosion-resistant coating prepared by the preparation method according to any one of claims 8 to 9 in the corrosion protection of cement-based concrete structures.